Structure and function of poly(3-hydroxybutyrate) depolymerase from Alcaligenes faecalis T1. - Nojiri, M (1997)
Poly(3-hydroxybutyrate) (PHB) depolymerase from Alcaligenes faecalis T1 is composed of three domains: the catalytic (C) domain, the fibronectin type III-like (F) domain, and the substrate-binding (S) domain. We constructed domain deletion, inversion, chimera, and extra-F-domain mutants and examined their enzyme activity and PHB-binding ability. In addition, we performed substitution of 214Asp and 273His with glycine and aspartate, respectively, to examine their participation in a catalytic triad together with 139Ser. The mutant with both the F and S domains deleted and the trypsin-digested enzyme showed no PHB-hydrolyzing activity and less PHB-binding ability than that of the wild-type enzyme but retained D-(-)-3-hydroxybutyrate trimer-hydrolyzing activity at a level similar to that of the wild-type enzyme. The mutant with the F domain deleted and the mutant which had the order of the F and S domains inverted retained PHB-binding ability and trimer-hydrolyzing activity at levels similar to those of the wild-type enzyme but lost PHB-hydrolyzing activity. The chimera mutant, in which the F domain was substituted with a Thr-rich domain of PHB depolymerase A from Pseudomonas lemoignei, and the extra-F-domain mutant, with an additional F domain, retained trimer- and PHB-hydrolyzing activities and PHB-binding ability at levels similar to those of the wild-type enzyme. Two mutants (D214G and H273D) showed no enzymatic activity toward trimer and PHB, and they were not labeled with [3H]diisopropylfluorophosphate.